PENGELOLAAN PAJAK HOTEL DAN PAJAK RESTORAN - Sahat Pardomuan Simbolon; Meyzi Heriyanto; Febri Yuliani (Universitas Riau, 2018)
Management of Hotel Taxes and Restaurant Taxes. This study aims to find out hoteland restaurant taxes in order to increase the Regional Original Income Pelalawan District. Thistype of research is qualitative. The research informant is Head of Secretary of BPKAD, Head ofDivision and Taxpayer. Technical data are interviews and documentation studies. Data analysisusing interactive models. The results showed that the constitution of hotel and restaurant taxmanagement on the Realization of Pendapatan Asli Daerah (PAD) is still very minimum.